Effects of 0.01 mM strontium on human periodontal ligament stem cell osteogenic differentiation via the Wnt/-catenin signaling pathway - Tongke Sun; Dan Ma; Yang Song; Jing Hu; Ziqing Yang; Xu Wang; Jun Zhang (Journal of International Medical Research)
Objectives Strontium (Sr 2+ ) is a crucial trace element in humans, mainly present in the bones. We investigated the effects of Sr 2+ on human periodontal ligament stem cell (hPDLSC) proliferation and osteogenesis and the relevant pathways. Methods hPDLSCs were harvested from extracted premolars and characterized by flow cytometry, then cultured and treated with various Sr 2+ concentrations. Cell-counting kit-8 (CCK-8) assays were used to assess hPDLSC proliferation, with alkaline phosphatase (ALP) staining, Alizarin red S staining, and ALP activity assays used to analyze their osteogenic capacity. Quantitative reverse transcription polymerase chain reaction and western blots were used to examine the expression levels of relevant factors, such as collagen I (COL-1), ALP, and Runx family transcription factor 2 (RUNX2). Moreover, tankyrase inhibitor XAV939 treatment was used to investigate the role of Sr 2+ in the canonical Wnt/β-catenin signaling pathway. Results The hPDLSCs were successfully isolated and cultured in vitro . A 0.01 mM Sr 2+ concentration significantly enhanced hPDLSC proliferation and osteogenic differentiation. However, XAV939-mediated inhibition of the canonical Wnt/β-catenin pathway could reverse the Sr 2 + -induced osteogenic effects. Conclusions Sr 2+ can enhance hPDLSC proliferation and osteogenesis by stimulating canonical Wnt/β-catenin signaling, suggesting it may play a critical role in periodontal regeneration and has clinical application potential.